Proposta de protocolo de implementação do Building Information Modeling (BIM) para os Institutos Federais de Educação, Ciência e Tecnologia - Paula, Lucimar de Souza e (2025)
Building Information Modeling (BIM) has become, since the early 2000s, one of the main drivers of digital transformation in the construction industry, although its adoption remains uneven across countries, sectors, and institutions. In Brazil, while public policies such as the BIM BR Strategy have established guidelines for its dissemination, effective implementation in the public sector is still marked by technical, cultural, and organizational barriers. In this context, the Federal Institutes of Education, Science, and Technology (IFs) constitute a strategic environment for innovation due to their national scope and relevance in managing educational infrastructure. This study aimed to develop and validate a BIM implementation protocol for the physical infrastructure of the IFs, with potential for adaptation by other public institutions. The research followed the Design Science Research (DSR) method, which combines scientific rigor with practical applicability in designing artifacts to solve organizational problems. The methodology comprised: (i) a scoping and documentary review of national and international guides, manuals, and protocols to identify recurring best practices and applicable guidelines; (ii) an exploratory survey with engineering and architecture professionals from 38 IFs to diagnose practices, maturity levels, and institutional challenges; and (iii) the development and subsequent validation of the proposed protocol by BIM experts, ensuring refinement and validation of the artifact. The results revealed recurrent challenges such as lack of training, cultural resistance to change, limited interoperability, and budget constraints, along with best practices consolidated into 18 key items related to governance, standardization, capacity building, and collaborative information management. The proposed protocol—modular in structure and supported by flowcharts, clearly defined roles, and monitoring stages—proved applicable and adaptable to institutional realities. It was recognized by experts as a clear, feasible methodological guide that supports decision-making. This study contributes to scientific advancement by bridging theory and practice in building a reference model for BIM implementation in the public sector, and offers practical contributions by providing a management tool for Federal Institutes and other public bodies. By reinforcing the importance of digital transformation in public construction, the work expands the debate on innovation, transparency, and efficiency in the sector, paving the way for future research and large-scale applications.